FAILURE ANALYSIS OF SCREW COMPRESSOR AND ITS MODIFICATIONS - Aat Safaat; Alfian Noviyanto (Universitas Mercu Buana, 2021)
Screw compressor is one of critical equipment at many industries. Therefore, its reliability and performance shall be maintained. One problem that often arises with screw compressors is the lubrication system. This study investigates the cause of the screw compressor failure and its modification to prevent failure in the future. The failure analysis of the screw compressor was successfully conducted using the fishbone analysis diagram and visual examination. The presence of water in the oil was found due to a change of oil color. The water content analysis showed that 6% of water was found in the oil in the third month. Indeed, the presence of water has a detrimental effect on the screw compressor part, showing that corrosion has occurred in the inner part of the screw ompressor element. We found the water source comes from the air due to high humidity. Therefore, modification in the air supply is needed to prevent water contamination in the oil. The air supply modification is done using dry air at the screw compressor outlet, flowing into the breather system. The modification results showed that the oil's water content decreased significantly from 6% to 0.0035%. In addition, the vibration that occurs decreases from 80 dB to 58 dB. This shows the effectiveness of the modification process to extend the life of the tool and maintain the plant's operational continuity.